2019
DOI: 10.1101/765321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An environmental DNA tool for monitoring the status of the Critically Endangered Smalltooth Sawfish, Pristis pectinata, in the Western Atlantic

Abstract: AbstractThe Critically Endangered Smalltooth Sawfish, Pristis pectinata, was once widespread in the tropical and subtropical waters of the Atlantic Ocean, but following substantial declines over the past century, the core population is currently confined to southwest Florida in the U.S. and the Bahamas. Recent research and verified public encounter reports suggests that this core population may be stabilizing and, potentially, expanding into formerly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The significant positive relationships observed between eDNA concentration and CPUE for qPCR and tNGS assays support the use of eDNA as a metric for species abundance, an important result that has been established in multiple previous studies and confirmed here for green crab (Doi et al, 2017; Knudsen et al, 2019; Lacoursière-Roussel et al, 2016; Lehman et al, 2019; Shelton et al, 2019). The tNGS method shows higher precision relative to qPCR for predicting CPUE, and this difference is most apparent at low abundances where the predicted abundance (CPUE) confidence interval for tNGS is much smaller than qPCR.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The significant positive relationships observed between eDNA concentration and CPUE for qPCR and tNGS assays support the use of eDNA as a metric for species abundance, an important result that has been established in multiple previous studies and confirmed here for green crab (Doi et al, 2017; Knudsen et al, 2019; Lacoursière-Roussel et al, 2016; Lehman et al, 2019; Shelton et al, 2019). The tNGS method shows higher precision relative to qPCR for predicting CPUE, and this difference is most apparent at low abundances where the predicted abundance (CPUE) confidence interval for tNGS is much smaller than qPCR.…”
Section: Discussionsupporting
confidence: 87%
“…The application of eDNA is generally limited to presence/absence surveys, but eDNA has shown to be positively correlated with species abundance in laboratory and field-based surveys (Doi et al, 2017; Knudsen et al, 2019; Lacoursière-Roussel et al, 2016; Lehman et al, 2019; Shelton et al, 2019). High variation in quantitative results from field surveys and a lack of rigorous validation in controlled laboratory settings have lead to considerable scrutiny of these methods (Mauvisseau, Burian, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the rarity of shark eDNA targets and the limitations of real-time PCR we suggest that future applications of this and similar assays should use digital droplet PCR (ddPCR) 54 for the high resolution quantification of rare target eDNA. This has recently been trialed for the detection of elasmobranch eDNA 20,23,55 , but has yet to be implemented for the spatio-temporal tracking of abundance.…”
Section: Discussionmentioning
confidence: 99%
“…However, community-based approaches and opportunistic catch data is often of low-resolution. Further, designation of important habitat is often done without the opportunity for thorough assessment of local behavior and ecology, as evidenced by habitat designation of the smalltooth sawfish in the United States which is only now being supplemented by direct studies of movement and location using telemetry (Wiley & Simpfendorfer, 2010; Norton et al, 2012; Graham et al, 2020), and presence/absence studies using environmental DNA (eDNA) techniques (Simpfendorfer et al, 2016; Lehman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%